Simulación de un algoritmo predictivo para la toma de decisiones en vertical HANDOVER para redes 4G LTE y Satelitales - Caisaguano Vega, Blanca Cecilia (2025)
Signal quality in mobile devices is an important factor that determines the efficiency and reliability of wireless communications. Within the improvement of communication systems, Vertical Hand Over is a critical process in network management, which allows the fluid transfer from one network connection to another. In the present study, the simulation of a predictive algorithm for vertical handover decision-making for 4G LTE and Satellite networks was carried out, for which parameters such as latency, BER, SNR, signal level, and quality were identified. signals of a wireless system were also considered. A simulation was generated in Matlab for the collection of 3000 data points that allows the estimation of these parameters based on the distance with respect to the network. Simulation tests of the predictive algorithm showed an accuracy of 80% and a precision of 96.9%, demonstrating a reliable system that allows the correct prediction of the Vertical Hand Over in the analysed networks based on the detected quality parameters.